Analysis The Effectiveness of Reading Park Management in Increasing Reading Interest in Bogor Regency - Syarifudin Yunus; Didik Notosudjono; Martinus Tukiran (International Journal of Educational Research, 2024)
Community reading parks have a role in increasing reading interest. This study measures the level of effectiveness of reading park governance, with the CIPP ( Context, Input, Process, Product ) model qualitatively. The instruments used include document studies, interviews, questionnaires, observations, and focus group discussions . Data analysis is analytical in nature. interactive. It can be concluded that the level of effectiveness of the management of reading parks in increasing public interest in reading is classified as "sufficient", with a score of 3.56 . The budget is the main obstacle for reading parks, in addition to policy implementation and human resources. The source of funds for reading parks, it turns out, is 75% from own funds, while the book collection of less than 3,000 books reaches 85%. Therefore, the management of reading parks must be further optimized.